Metal−organic frameworks self-templated cubic hollow Co/N/C@MnO2 composites for electromagnetic wave absorption. (January 2020) - Wang, Ruili; He, Man; Zhou, Yuming; Nie, Shuangxi; Wang, Yongjuan; Liu, Wenqi; He, Qiang; Wu, Wenting; Bu, Xiaohai; Yang, Xiaoming
Abstract: Green and facile strategies for fabricating hollow microwave absorption materials without harmful solvent etching have attracted extensive attention but still remain a challenge. Herein, the cubic hollow Co/N/C@MnO2 composites were prepared through metal–organic frameworks (MOFs) self-templated eco-friendly method with polydopamine (PDA) as carbon source and hierarchical MnO2 nanosheets were incorporated for improving impedance mismatch caused by excessive permittivity in Co/N/C. Such a uniform distribution of Co particles in the N-doped porous carbon matrix, in association with the hollow structure and hierarchical MnO2 nanosheets, endow the composites with enhanced electromagnetic (EM) wave absorption. Notably, Co/N/C@MnO2 sample with a filler loading of 15 wt% shows extraordinary EM wave absorbing performance with the minimum reflection loss (RL) of −58.9 dB and wide absorption bandwidth of 5.5 GHz. Several minimum RL values at a thickness in the range of 1.5–5 mm, are below than −50 dB, outperforming many similar materials reported previously. Besides, the possible microwave absorption mechanism was elaborated in detail. Our work provides an environmentally friendly and facile route for fabricating MOFs self-templated hollow carbon-based microwave absorbers. Graphical abstract: Metal−organic frameworks self-templated cubic hollow Co/N/C@MnO2 composites shows extraordinary electromagnetic wave absorbing performance due to synergetic effects of optimal impedance match and excellent EM attenuation ability. Image 1